Myanmar Economic Monitor, June 2019 : Building Reform Momentum - World Bank (World Bank, Washington, DC, 2019)
Myanmar's economy is slowly picking up speed and regaining stability after a volatile 2018. Despite a challenging global environment, Myanmar's economic growth is expected to rise to 6.5 percent in 2018/19 from 6.4 percent in the Transition Period1 supported by strong performance in the manufacturing and services sectors. Volatility that buffeted the economy in 2018 has started to ease. Inflation moderated, the kyat stabilized, and fuel prices fell in Q1 2018/19, though there have been some reversals in prices in Q2. The economic outlook looks positive, with growth expected to reach 6.7 percent in the medium-term. The recent decisions to ease trade restrictions; open the financial sector to greater foreign competition; and begin mega infrastructure projects signal a decisive and awaited uptick in reform momentum. Downside risks to the economic outlook are driven by external factors, including possible revocation of preferential trade access under the European Union Generalized System of Preferences. Slowing global and regional growth, especially in China, together with renewed escalation of global trade tensions, could also slow exports and the flow of inbound foreign investments. Insecurity in border areas, the Rakhine crisis, with violence and forced displacement of refugees, and the recent flare-up in violence involving the Arakan Army, could affect investors' sentiment. The 2020 general election is also a source of uncertainty.